Peculiar Expression of CD3-Epsilon in Kidney of Ginbuna Crucian Carp - Miyazawa, Ryuichiro; Murata, Norifumi; Matsuura, Yuta; Shibasaki, Yasuhiro; Yabu, Takeshi; Nakanishi, Teruyuki (Frontiers in Immunology, 2018)
TCR/CD3 complex is composed of the disulfide-linked TCR-αβ heterodimer that recognizes the antigen as a peptide presented by the MHC, and non-covalently paired CD3γε- and δε-chains together with disulfide-linked ζ-chain homodimers. The CD3 chains play key roles in T cell development and T cell activation. In the present study, we found nor or extremely lower expression of CD3ε in head- and trunk-kidney lymphocytes by flow cytometric analysis, while CD3ε was expressed at the normal level in lymphocytes from thymus, spleen, intestine, gill and peripheral blood. Furthermore, CD4-1+ and CD8α+ T cells from kidney express Zap-70 but not CD3ε, while the T cells from other tissues express both Zap-70 and CD3ε, although expression of CD3ε was low. Quantitative analysis of mRNA expression revealed that the expression level of T cell-related genes including tcrb, cd3ε, zap-70 and lck in CD4-1+ and CD8α+ T cells was not different between kidney and spleen. Western blot analysis showed that CD3ε band was detected in the cell lysates of spleen but not kidney. To be interested, CD3ε-positive cells greatly increased after 24 hours in in vitro culture of kidney leukocytes. Furthermore, expression of CD3ε in both transferred kidney and spleen leukocytes was not detected or very low in kidney, while both leukocytes expressed CD3ε at normal level in spleen when kidney and spleen leukocytes were injected into the isogeneic recipient. Lower expression of CD3ε was also found in kidney T lymphocytes of goldfish and carp. These results indicate that kidney lymphocytes express no or lower level of CD3ε protein in the kidney, although the mRNA of the gene was expressed. Here we discuss this phenomenon from the point of function of kidney as reservoir for T lymphocytes in teleost which lacks lymph node and bone marrow.